The Rule of Law: Measurement and Deep Roots - Jerg Gutmann; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper does three things. First, based on a limited number of theoretically established dimensions, it proposes a new de facto indicator for the rule of law. It is the first such indicator to take the quality of legal norms explicitly into account. Second, using this indicator we shed new light on the relationship between the rule of law and the political system of a country. Presidential governments tend to score significantly lower on the rule of law indicator than parliamentary ones. Many presidential democracies are even outperformed by dictatorships. The observation that political systems hardly predetermine the rule of law level raises the question why the authority of law differs across societies in its capacity to constrain the behavior of public officials. Third, because of this question, we investigate the roots of the rule of law. As theory on this specific question is scarce and the rule of law is closely associated with income levels, we draw on a topical literature that deals with the fundamental causes of economic development. Our findings suggest that specific determinants of long-run development operate via the rule of law, whereas others are not related to the rule of law at all. Our empirical evidence does, however, support not only the “primacy of institutions” view, but also the important role that human capital, which European settlers brought to their colonies, played in historical economic development.
Keywords: B41; C81; C82; H11; K00; O17; O43; O57; 330; rule of law; democracy; dictatorship; economic development; geography; institutions